1983
DOI: 10.1111/j.1468-2958.1983.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

INTERPERSONAL PERCEPTION BETWEEN INTIMATES An Integrative Review

Abstract: Despite the considerable importance often attributed to interpersonal perception between married partners. family members, and other intimates, there have been few theoretical developments that address the distinctive factors agecting perception in these contexts. This article draws upon a broad literature review to suggest how interpersonalperception between intimates may be affected by such factors as familiarity, emotionality. behavioral interdependence. and ideological beliefs about intimacy. Particular at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 77 publications
6
108
0
Order By: Relevance
“…This effect is referred to as bias. Bias, as it is understood in the person perception literature, does not inherently imply error; but can have accuracyenhancing effects 23,28) as is the case when individuals do not always have all the information they need to make a judgment about a partner's feelings and experiences 27) . For this reason, we expect a positive relationship between self-and partner-ratings of work-family conflict but not a high overlap between both ratings.…”
Section: Bakker Et Almentioning
confidence: 99%
“…This effect is referred to as bias. Bias, as it is understood in the person perception literature, does not inherently imply error; but can have accuracyenhancing effects 23,28) as is the case when individuals do not always have all the information they need to make a judgment about a partner's feelings and experiences 27) . For this reason, we expect a positive relationship between self-and partner-ratings of work-family conflict but not a high overlap between both ratings.…”
Section: Bakker Et Almentioning
confidence: 99%
“…In an important early literature review, Sillars and Scott (1983) noted that, in studies of couples engaged in conflict interactions, married partners who are closer and happier actually display less empathic accuracy than those who are not. In 4 related research, Sillars et al (1984) found that more negative statements and more negative vocal tones were expressed by spouses who more accurately discerned how their partner assessed the importance of the problems being discussed.…”
Section: A Test Of the Empathic Accuracy Model In Marital Interactionsmentioning
confidence: 99%
“…In writing about the relationship between agreement and accuracy in marital dyads, Sillars et al (1984) feel that accuracy may be confounded with agreement through projection of one's own views on the other and various response sets. In the case of work dyads there is no empirical evidence about the role of projection per se, however the present study presents evidence for the first time that…”
Section: Implications Of Present Studymentioning
confidence: 99%
“…Based on findings in their work with marital dyads, Sillars et al (1984), claim that agreement within a dyad is confounded in some ways with accuracy in predicting the partner's perception. For example, they maintain that, "Couples who have a high level of agreement may guess one another's response via projection or the imputation of a similar response to the partner" (Sillars et al 1984, p. 319).…”
mentioning
confidence: 99%